Restless Legs Syndrome and Erectile Dysfunction - Gao, Xiang (Associated Professional Sleep Societies, LLC, 2010)
STUDY OBJECTIVES: Dopaminergic hypofunction in the central nervous system may contribute to restless legs syndrome (RLS) and erectile dysfunction (ED). We therefore examined whether men with RLS have higher prevalences of ED. DESIGN: RLS was assessed using a set of standardized questions. Men were considered to have RLS if they met 4 RLS diagnostic criteria recommended by the International RLS Study Group, and had restless legs ≥ 5 times/month. Erectile function was assessed by a questionnaire. SETTING: Community-based. PARTICIPANTS: 23,119 men who participated in the Health Professional Follow-up Study free of diabetes and arthritis. RESULTS: Multivariate-adjusted odds ratios for ED were 1.16 and 1.78 (95% confidence interval: 1.4, 2.3; P trend < 0.0001) for men with RLS symptoms 5–14 times/mo, and 15+ times/mo, respectively, relative to those without RLS, after adjusting for age, smoking, BMI, antidepressant use, and other covariates. The associations between RLS and ED persisted in subgroup analysis according to age, obesity, and smoking status. CONCLUSIONS: Men with RLS had a higher likelihood of concurrent ED, and the magnitude of the observed association was increased with a higher frequency of RLS symptoms. These results suggest that ED and RLS share common determinants. CITATION: Gao X; Schwarzschild MA; O'Reilly EJ; Wang H; Ascherio A. Restless legs syndrome and erectile dysfunction. SLEEP 2010;33(1):75-79.